Trends in the development of education in Kazakhstan (Herald of Journalism, 2016)
Purpose – the implementation of social analysis of global trends in national education. Methodological basis for a philosophy of education, primarily through the interaction of its aspects as an ontological (studythe essence and content of education and science in the context of social life); axiological (defining core values , the specificity of their modern transformation). The study used the method of qualitative andquantitative analysis of the text content of the media. Original/value. Relevance and significance of trends in the development of innovations in education in Kazakhstan explained the new stage in the developmentof our country, based on the rapid progress of the country in the Community 30 most competitive countries in the world.Findings. Has a deep relationship of the nature of social relations and the development of the system characteristics of the theory and practice of education; proved that the education system should take intoaccount accumulated by generations of cultural experience.
Keywords: education; science; religion; mass media